Accessory ovarian steroid cell tumor producing testosterone and cortisol: A case report. Issue 37 (September 2017) - Zang, Li; Ye, Mingxia; Yang, Guoqing; Li, Jinlong; Liu, Mei; Du, Jin; Gu, Weijun; Jin, Nan; Yang, Lijuan; Ba, Jianming; Dou, Jingtao; Fan, Wensheng; et al.
Abstract: Rationale: An accessory ovary is a rare structure containing normal ovarian tissue, which has a direct or ligamentous connection with a normal and eutopic ovary. Patient concerns: In the study, we reported a 46-year-old woman presented with secondary amenorrhea and virilization symptoms for 1 year. Diagnoses: Endocrine evaluation revealed slightly elevated serum cortisol, extremely elevated 24-hour urinary-free cortisol and serum testosterone. Clinical assessment exhibited a large solid mass with heterogeneous enhancement in the left adnexauteri compounded with hypercortisolism and hyperandrogenemia. An accessory ovarian tumor attached to the infundibulum of the left fallopian tube was found, and a separate normal ovary was present on the same side. Interventions: The patient underwent a left adnexectomy. Outcomes: During surgery, a 12 cm × 8 cm, gray-red, and well-circumscribed solid mass was be identified. The tumor had ligamentous attachment with the infundibulum of left fallopian tube. The sectioned surface was gray-brown, lobulated and did not exhibit either significant necrosis or hemorrhage. Pathological findings demonstrated that tumor cells had small round nuclei, mild atypia, no mitosis were arranged in a diffuse pattern of columns or nests separated by a rich vascular network and no crystals of Reinke were found. It was diagnosis ovarian steroid cell tumor (NOS) without malignant behavior by immunohistochemical staining. The patient was finally diagnosed as accessory ovarian steroid. The patient was discharged from the hospital on the seventeenth day after surgery. During postoperative follow-up, the first postoperative menstrual flow recovered and blood pressure regained 1 month after surgery. Furthermore, her Cushing syndrome regressed and hirsutism disappeared completely 4 months after surgery cell tumor. Lessons: It is vitally important to establish a final diagnosis according to the clinical manifestations and laboratory values in addition to imaging studies and laparoscopic examination of a rare coexistence of hyperandrogenemia and Cushing syndrome based on the accessory ovarian pathology.